Estradiol Meets Notch Signaling in Developing Neurons - Arevalo, Maria-Angeles; Ruiz-Palmero, Isabel; Simon-Areces, Julia; Acaz-Fonseca, Estefania; Azcoitia, Iñigo; Garcia-Segura, Luis M. (Frontiers in Endocrinology, 2011)
The transmembrane receptor Notch, a master developmental regulator, controls gliogenesis, neurogenesis, and neurite development in the nervous system. Estradiol, acting as a hormonal signal or as a neurosteroid, also regulates these developmental processes. Here we review recent evidence indicating that estradiol and Notch signaling interact in developing hippocampal neurons by a mechanism involving the putative membrane receptor G protein-coupled receptor 30. This interaction is relevant for the control of neuronal differentiation, since the downregulation of Notch signaling by estradiol results in the upregulation of neurogenin 3, which in turn promotes dendritogenesis.